NONLOCAL MULTIPOINT (IN TIME) PROBLEM WITH OBLIQUE DERIVATIVE FOR A PARABOLIC EQUATION WITH DEGENERATION - Pukalsky, Ivan; Yashan, Bohdan (Journal of Mathematical Sciences, 2020)
For a second-order parabolic equation, we consider a multipoint (in time) problem with oblique derivative. The coefficients of the equation and boundary condition have power singularities of any order in time and spatial variables on a certain set of points. We establish conditions for the existence and uniqueness of solution of the posed problem in Hölder’s spaces with power weight.